Chronic energy malnutrition in mothers associated with stunting - Alfi Fairuz Asna; Muh. Nur Hasan Syah (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2023)
Background: Stunting is a nutritional problem that has a long-term impact. It has an impact on children's cognitive and physical development, serious infections, and makes a significant contribution to mortality and morbidity. According to WHO, the stunting rate in Indonesia is still high (30.8%). Maternal nutritional status contributes to fetal growth restriction which increases the risk of low birth weight and increases the risk of stunting. Objectives: This study aims to determine the relationship between maternal nutritional status during pregnancy and stunting in children aged 6-23 months in Karawang Regency. Methods: This study is an observational study with a cross-sectional design. The number of samples was 207 children aged 6-23 months in Srikamulyan village, Karawang regency. Data were collected using a structured questionnaire to determine the identity of the child, the identity of the mother, the nutritional status of the child, the history of the nutritional status of the mother during pregnancy, and sociodemographic data. Anthropometric measurements of the mother's height using a microtoise and the child's body length using a length board. Data were analyzed using univariate and bivariate analysis. Results: The results showed that as many as 23.67% of children aged 6-23 months experienced stunting in Srikamulyan Village. Mothers who experience Chronic Energy Malnutrition during pregnancy as much as 8.2%. Data analysis showed that mothers with Chronic Energy Malnutrition during pregnancy were associated with stunting in children aged 6-23 months (p<0.05).Conclusions: Chronic Energy Malnutrition during pregnancy is associated with the incidence of stunting in children aged 6-23 months. Prevention efforts from adolescent girls are an important key in improving the nutritional status of women of childbearing age and pregnant women in order to prevent stunting